A ratiometric fluorescent probe based on peptide modified MnFe2O4 nanoparticles for matrix metalloproteinase-7 activity detection in vitro and in vivo. Issue 8 (25th March 2022) - Chen, Hongda; Zhang, Hua; Wang, Zhenxin
Abstract : A peptide modified MnFe2 O4 ratiometric fluorescent nanoprobe is developed for noninvasively visualizing the distribution of matrix metalloproteinase-7 in vitro and in vivo . Abstract : Abnormal expression of matrix metalloproteinases plays an important role in tumor invasion and metastasis. In this report, a peptide modified MnFe2 O4 ratiometric fluorescent nanoprobe is developed for noninvasively visualizing the distribution of matrix metalloproteinase-7 (MMP-7) in vitro and in vivo . A fluorescein isothiocyanate (FITC) modified peptide containing the specific motif VPLSLTMG for MMP-7 cleavage was conjugated with MnFe2 O4 nanoparticles (NPs) to establish a Förster resonance energy transfer (FRET) system for sensing the protease. The rhodamine B (RhB) modified targeting peptide immobilized on the nanoparticle surface was not only used as an internal reference for forming a ratiometric fluorescence system together with the FITC dye, but also used for enhancing the tumor targeting ability. The tumor accumulation amount of the as-developed ratiometric fluorescent probe (termed MnFe2 O4 -pep-dyes) can be measured by T 2 -weighted magnetic resonance ( T 2 -weighted MR) imaging because MnFe2 O4 NPs display an excellent T 2 -weighted MR contrast ability. In the presence of MMP-7, FITC detached from the MnFe2 O4 surface resulting in the recovery of FITC fluorescence, while no obvious change of the RhB fluorescence was observed. The recovery ratio of FITC to RhB fluorescence intensity is linearly dependent on the MMP-7 concentration within the range of 0.1 to 15 nM in buffer and 5 × 10 2 to 1 × 10 4 cells in cell lysates with a limit of detection of 0.1 nM and 436 cells, respectively. MnFe2 O4 -pep-dyes was further applied to spatially observe MMP-7 expression in a tumor-bearing mouse by in vivo fluorescence imaging with external magnetic field assistance for demonstrating its practicability.